La formulación clínica en psicooncología: un caso de depresión, aversión a alimentos y problemas maritales en una paciente de cáncer de mama - Cruzado, Juan A. (Psicooncología, 2006)
The clinical case formulation in Psycho-Oncology is necessary to determine causes of the problems of patients, to plan the most effective intervention and to evaluate its outcomes. A model of clinical formulation case is especially useful to organize the complex information, improve communication between professionals, research the reliability and optimize supervision. It is exposed a model of case formulation that is based in the guidelines with best clinical and empirical support. The formulation model is illustrated with the exposition of a clinical case: a woman suffering depression, aversion to specific foods and marital problems after having been treated for breast cancer by means of mastectomy, chemotherapy and hormonal therapy. The case formulation is exposed step by step.